Trends in research related to vaccine and cancer prevention from 1992 to 2022: A 30-years bibliometric analysis - Luofei Zhang; Kefu Yu; Bin Zhu; Shenghui Mei; Jiping Huo; Zhigang Zhao (Taylor & Francis Group, 2023)
Vaccines may play an important role in cancer prevention. This bibliometric study in the field of vaccine and cancer prevention is designed to evaluate key research advances, identify existing deficiencies, and provide reference for future investigations. A total of 2916 original articles published in English from 1992 to 2022 were extracted from the Web of Science core collection. America (1,277) and the National Cancer Institute (82) were the most productive country and institution in this field, respectively. Vaccine was not only the most co-cited journal but also the most influential. Garland SM was the most prolific author, and Bosch FX was the most influential co-cited author. The keywords "cervical cancer" had the highest frequency. "Nanovaccines," "vaccine acceptance" and "coverage" were the new research hotspots in this field. Currently, although an increasing number of publications involve vaccine and cancer prevention studies, most of them are related to cervical cancer, and few other cancers, suggesting the need to investigate other cancer prevention vaccines. The promising research hotspots, such as nanovaccines, vaccine acceptance, and vaccine coverage should be the focus of investigation. The study provides the current status and trends in clinical research on vaccine and cancer prevention, enabling researchers to identify hotspots and explore new study directions. In the future, vaccines are expected to play a key role in multiple cancer prevention.